FORMATION, TAPHONOMY AND DATING OF THE NEOLITHIC LAYER OF THE CHOKH SETTLEMENT: DATA REVISION - Amirhanov, Hizri Amirhanovic (History, Archeology and Ethnography of the Caucasus, 2021)
To date, sixty years have passed since the excavations of V. G. Kotovich at the Chokh settlement and almost forty years after the fieldwork was carried out there by the author. Over these decades, much has changed in the approaches to excavations and to the interpretation of materials obtained from layers with heterogeneous archaeological stratigraphy and complex lithological structure. A new understanding of the Chokh materials leads to the need to revise some of our ideas about the formation, taphonomy and relative chronology of finds and objects of the Neolithic layer of this site. With regard to the Chokh settlement, such an analysis leads to the need to consider the layer C (Neolithic) as a multi-component cultural and geological formation consisting of three or four consecutive microstratigraphic divisions. Based on this, an attempt is made in this paper to correct the ideas concerning the composition of archaeological material belonging specifically to the Neolithic layer. Special attention is paid to the highlighting of the homogeneous part that is related with the “floor” of the cultural layer C, or, in other words, the lowest, initial horizon (layer C, “bottom” or layer C, horizon 3), of which the formation of the Neolithic layer began. The breakdown of the cultural layer C into different living surfaces is carried out by linking the latter to the levels of occurrence of hearths and fire pits. This makes it possible, in particular, to isolate a homogeneous part of the material that is associated with the “floor” of the layer under consideration (layer C, “bottom” or layer C, horizon 3). In this paper, we have tried to isolate from the totality of the archaeological material of Layer C, its various parts, which can be attributed to the Neolithic layer with varying degrees of confidence.